Periodic Orbits for a Three-Dimensional Biological Differential Systems - Renato Colucci; Daniel Nuñez (Abstract and Applied Analysis)
We study the existence of periodic orbit for a differential system describing the effects of indirect predation over two preys. Besides discussing a generalized version of the model, we present some remarks and numerical experiments for the nonautonomous version of the two models.